Zwalczajmy pijaństwo!. (Gdańsk : [s.n.], 1954)
Afisz kampanii antyalkoholowej.
Keywords: Alkoholizm -- zapobieganie -- Polska -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- druki ulotne